Combining ability × environment interaction and genetic analysis for agronomic traits in safflower (Carthamus tinctorius L.): biplot as a tool for diallel data - Pooran Golkar; Ehsan Shahbazi; Mojtaba Nouraein (Acta Agriculturae Slovenica)
Combining ability × environment interaction is considerable to identify the effect of environment on the combining ability and gene action of the traits to select appropriate parents for safflower hybrid production. The 36 genotype (28 F2 progenies of eight-parent half-diallel crosses across 8 parental genotypes) of safflower were studied to investigate the mentioned parameters across different geographical regions of Iran. The results indicated significant differences among parents for general and specific combining ability, except for seeds per capitulum across three environments. The overall results indicated that K21 and Mex.22-191 were excellent parents with greater general combining ability for the improvement of seed yield in safflower. The K21 × Mex.22-191 hybrid could be, therefore, employed for the production of high seed yield in safflower breeding. The estimates of genetic variance components recommended the importance of additive- dominance genetic effects that contributed to variation in yield per plant. Such gene action expression for seed yield needs auxiliary methods based on hybridization and selection for seed yield advancement in safflower.